Influence of Socio-Psychological Factors on Consumer Willingness to Pay (WTP) for Organic Food Products - Baiyegunhi, Lloyd J.S.; Mashabane, Sikhumbuzo E.; Sambo, Nonjabulo C (Journal of Economics and Behavioral Studies, 2018)
This study evaluates consumers’ willingness to pay (WTP) a premium for organic vegetables and fruits in Pietermaritzburg metropolis, KwaZulu-Natal province, South Africa, using data collected from 210 consumers approached during their food shopping. The standard economic approach to valuation was extended by including psychological factors. The results from the empirical model show that psychological factors (behavioural control, attitude and subjective norms) exerted more influence on consumers’ WTP for organic products. In addition, socio-demographic factors such as gender, education, number of children in a household, high income and race, are statistically significant in explaining consumers’ WTP for organic food. Policy implications for advancement and improved promotion, sales and consumption of organic food products were discussed.